THE PRAGMATICS OF GENDER DIFFERENCES IN COMMUNICATION (Journal of Universal Science Research, 2025)
This research investigates the pragmatics issues of gender differences in communication from a linguistic and scientific approach focusing on discourse by men vs women. The study looks at speech acts, conversational styles and interactional norms to evaluate how language is differently made by men and women and whether these differences have consequences for the male and female communicators themselves. This presented thesis uses linguistic theory, gender studies and empirical data used for the over-arching understanding of gendered communication.